Study on bed load pattern at Lebir River after 2014 flood - Nur Insyirah Izzati, Omar (2016)
The purpose of this research was to identify the size and types of sediment at Lebir River after 2014 flood, to analyse the bed load discharge of Lebir River using selected method and to identify the sediment pattern/bed load pattern due to sedimentation process. The study conducted at 5 stations at Lebir River. The rainfall precipitation in December 2014 showed that the maximum rainfall event will cause the high amount of rainfall precipitation and will increase the production of bed load transport. Therefore, the surface erosion also gives contribution to the increase of sediment transport and had become the one of main problem at Lebir River after flood in December 2014. The bed load pattern at each point were identified through the sedimentation process. The bed load pattern gave the variation of sediment transport modes at Lebir River. The bed load discharge were evaluated using three different formulas which were Meyer Peter and Muller, Schoklitsch and Duboys equation. From the analysis of the results of each of the formula, Meyer Peter and Muller can be used to predict bed load transport for Lebir River.